The Challenges of Smart City Implementation in Indonesia: Case Study of Sleman Regency, Special Region of Yogyakarta, Indonesia (Journal of Governance and Development (JGD), 2019)
The cityâ€™s growth is accelerating, from year to year, the population in every city in the world increases drastically. This makes the cities in the world have the advantages as well as the challenge in facing the problem. Urban-speciï¬c problems such as congestion, ï¬‚ooding, public services that are not maximally controlling unstable resources are a problem to be solved together. Smart city concept is present to answer the challenge. By bringing forward effective city concepts and efï¬cient smart city to be a new prima donna for every regional leader to be implemented. In Indonesia alone, smart city has begun in the adoption by many big cities, such as Jakarta, Bandung Surabaya, Makassar, and others. In Indonesia the government has also implemented the movement of 100 smart cities in Indonesia. In the year 2017 there are 24 districts that participated in the movement, including Sleman District. Sleman District is a district with a vision and mission in line with the concept of the smart city. In Sleman smart city application has been running for quite a while. But of course, in the application of the concept, there are many challenges that must be resolved by the government, such as community culture in using the internet, commitment from Government in its application and supporting technology realization intelligent district. This research departs from one of the important issues in Indonesia that a smart city, and also try to analyze the obstacles in the application of smart city, especially in Sleman regency. This research is library research with data collection was conducted through literature review by collecting various journal articles, websites, reports, and books. The collected data were then described and analyzed to satisfy the research purposes.